Protein Kinase C Isoforms Differentially Regulate Hypoxia-Inducible Factor-1 alpha Accumulation in Cancer Cells - Kim, Hyunju; Na, Yu-Ran; Kim, So Yeon; Yang, Eun Gyeong (WILEY-BLACKWELL, 2016)
Hypoxia-inducible factor-1 alpha (HIF-1 alpha) is one of the key transcription factors that mediate adaptation to hypoxia. Despite increasing evidence implicating the PKC family as potential modulators of HIF-1 alpha, the molecular mechanisms of PKC isoform-dependent HIF-1 alpha activity under hypoxic conditions have not been systematically elucidated in cancer cell lines. Here, we collectively investigated how each isoform of the PKC family contributes to HIF-1 alpha accumulation in the human cervical cancer cell line HeLa. Among the abundant PKC isoforms, blockade of either PKC alpha or PKC delta was found to substantially reduce HIF-1 alpha accumulation and transcriptional activity in hypoxic cells. Knockdown of PKC delta resulted in a reduction of HIF-1 alpha mRNA levels, whereas the HIF-1 alpha mRNA level was unchanged regardless of PKC alpha knockdown. Upon searching for the downstream effectors of these kinases, we found that PKC alpha controls HIF-1 alpha translation via AKT-mTOR under hypoxic conditions. On the other hand, one of the well-known transcriptional regulation pathways of HIF-1 alpha, nuclear factor-kappa B (NF-kappa B) is identified as a downstream effector of PKC delta. Taken together, our findings provide insights into the roles of PKC isoforms as additional, discrete modulators of hypoxia-stimulated HIF-1 alpha accumulation through different signaling pathways. (C) 2015 Wiley Periodicals, Inc.
Keywords: NF-KAPPA-B; GENE-EXPRESSION; PKC-DELTA; ENDOTHELIAL-CELLS; MAMMALIAN TARGET; TUMOR-SUPPRESSOR; HIF-ALPHA; ACTIVATION; HYPOXIA-INDUCIBLE-FACTOR-1-ALPHA; HIF-1-ALPHA